Understanding magnetic fields, for NMR/MRI - Mark S. Conradi (Journal of Magnetic Resonance Open, 2024)
The basic physics of magnetic fields is presented for a target audience of NMR workers. This group often does not have formal training in electromagnetism, but could benefit from an understanding of a selected subset of topics. The focus here is on a relatively non-mathematical view, intended to deliver an intuitive understanding of the topic. The covered topics start with the fields arising from simple idealized currents, including long straight wires, short flat coils, infinite current sheets, long solenoids, and magnetic dipole moments. The generation of field gradients and shim fields is discussed. All of these can be unified by considering the divergence and curl of the magnetic field. Magnetic materials are treated, both linear magnetizable materials (including the sample itself) and permanently magnetized materials; the approaches of equivalent currents and Ampere's theorem for magnetic circuits are presented.